Climatic framework of the end of the pleistocene and the Holocene: paleoclimatic variations during the last 35,000 years - Mörner, Nils-Axel (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Paleoclimatic changes are recorded by several methods. These fluctuations follow cycles of different rank and duration. Seen in a global scale, there can be little doubt that the climatic changes generally occurred simultaneously all over the globe. This does not mean that they are equally expressed; on the contrary, these changes are quite locally expressed. It is the coincidence in time that reveals the global climatic background. The Gothenburg Magnetic Excursion and Flip, characterized by Pacific VGP positions, provide a new tool for global correlations. The radiocarbon calibration scale is extended back at least to 10,000 BP via a new method based on shorelines and varves. Because of necessary good dating control, the present analysis is confined to the last 35,000 years. 1) Correlations of global climatic data indicate a worldwide synchronism without any detectable time-lag between different variables. 2) Climatic, glacial and eustatic fluctuations follow four main cycles: a 21,000-yr cycle, a 5250-yr cycle, an irregular 1000-3600-yr cycle, an irregular 230-1000-yr cycle. 3) Geoidal-eustasy is a new factor which is related to fundamental geophysical processes. 4) Integrated studies of multiple parameters in the same long Holocene sediment cores have revealed a detailed correlation between climatic changes, eustatic changes, paleomagnetic intensity and polarity changes, atmospheric 14C production changes, etc, suggesting a mutual origin. 5) The main cause of the 5250-yr cycle and the two irregular cycles seems to be changes of the core/ mantle coupling and interface according to two different systems. This explains the correlations established and the absence of any time-lag.